An experimental study of exenatide effects on renal injury in diabetic rats - Wang,Xiaodong (2019)
Abstract Purpose: To investigate the effects of exenatide on renal injury in streptozotocin-induced diabetic rats. Methods: Fifty SD rats were randomly divided into normal control, model, exenatide-1, exenatide-2 and exenatide-3 groups, 10 rats in each group. The diabetic nephropathy model was constructed in later 4 groups. Then, the later 3 groups were treated with 2, 4 and 8 μg/kg exenatide for 8 weeks, respectively. The serum and urine biochemical indexes and oxidative stress and inflammatory indexes in renal tissue were determined. Results: Compared to the model group, in exenatide-3 group the serum fasting plasma glucose and hemoglobin A1c levels were significantly decreased, the fasting insulin level was significantly increased, the renal index and blood urea nitrogen, serum creatinine and 24 h urine protein levels were significantly decreased, the renal tissue superoxide dismutase and glutathione peroxidase levels were significantly increased, the malondialdehyde level was significantly decreased, and the renal tissue tumor necrosis factor alpha, interleukin 6, hypersensitive C-reactive protein and chemokine (C-C motif) ligand 5 levels were significantly decreased P<0.05). Conclusions: Exenatide can mitigate the renal injury in diabetic rats. The mechanisms may be related to its resistance of oxidative stress and inflammatory response in renal tissue.